"A living archive of modern protest": Memory-making in the Women's March. (3rd April 2018) - Kitch, Carolyn
ABSTRACT: The Women's March, held on January 21, 2017, the day after Donald Trump's inauguration as President of the United States, made news across the world as a surprisingly powerful current event that signaled possible political and social futures. Yet this event was also threaded with the past. This essay examines the uses and constructions of memory in the marches and their mediation, drawing on news and social media coverage, on my own on-site experience at the Washington, DC, march, and interdisciplinary scholarship that may provide theoretical context for understanding the event's nature and lasting importance. It considers the rhetorical and material memory work, on the ground, of both the official ceremonies and the marchers' more vernacular expressions, as well as the complex interplay of mediation, resulting in definitions of the event as historic in its own right and as a map for the future.